Effect of Recombinant Human Amelogenin on the Osteogenic Differentiation Potential of SHED - Akira Hirabae; Ryo Kunimatsu; Yuki Yoshimi; Kodai Rikitake; Shintaro Ogashira; Ayaka Nakatani; Shuzo Sakata; Kotaro Tanimoto (Cells)
This study aimed to explore how amelogenin can improve stem cells from human exfoliated deciduous teeth (SHED)–based bone regeneration and promote tissue healing as a treatment for critical-sized bone defects. SHED was induced into bone differentiation by using osteogenic differentiation medium. Real-time polymerase chain reaction, alkaline phosphatase (ALP) staining and quantification, and Alizarin Red S staining, as well as calcium and osteocalcin quantification were performed to assess differentiation. On day 18, a significant increase was observed in the expression of RUNX2, CBFB, BGLAP, COL1, BMP2, BMP4, NOTCH1, NOTCH2, and NES. Osteocalcin gene expression continued to increase significantly. ALP activity was significantly higher in the amelogenin-treated group than in the control group on days 7, 10, and 14. On day 14, enhanced ALP staining was observed in the amelogenin-treated group. Calcium and osteocalcin levels were significantly higher in the amelogenin-treated group than in the control group on day 21. This study suggests that combining SHED and amelogenin may be effective for bone regeneration, offering a potential new approach in regenerative medicine.